Literatur Review: Sistem Pakar Untuk Mendiagnosis Gangguan Mental Menggunakan Metode Certainty Factor - Deny Bagus Septian; Firman Noer Rizal; Ahmad Taufiqi; Stevianus Imanuel Salangka; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
This literature review examines how expert systems that may detect mental diseases employ the Certainty Factor technique. Treatment for mental disorders is important because they are serious health issues. The Certainty Factor method has become one of the approaches employed in this expert system, which has been widely used as a tool for diagnosing mental diseases. This literature study aims to investigate the effectiveness and application of the Certainty Factor method in expert systems for diagnosing mental disorders. This method allows the assessment of the level of confidence in the various rules or facts that are relevant in the diagnosis. A literature review is carried out by collecting and analyzing related articles that have been published within a certain period of time. The results of this literature study indicate that the use of the Certainty Factor method in an expert system to diagnose mental disorders has a number of advantages. This method allows the representation of the degree of uncertainty and subjective judgment in the diagnostic process. This enriches the expert system's ability to consider various factors that influence the diagnosis of mental disorders. However, there are also several challenges in applying the Certainty Factor method in expert systems to diagnose mental disorders. Accurate determination of certainty factors can be subjective and requires deep expert expertise. In addition, ignoring the relationships and interactions between rules can also affect the accuracy of the resulting diagnoses. In order to increase the success of the Certainty Factor method in diagnosing mental disorders, this literature study recommends the need to improve the quality of knowledge and data used in expert systems. Periodic evaluation and updating also needs to be done to ensure the accuracy and reliability of the expert system.